Effects of acetylation and acetylation-hydroxypropylation (dual-modification) on the properties of starch from Carioca bean (Phaseolus vulgaris L.) - Granza, Andressa Gabardo; Travalini, Ana Paula; Farias, Fabiane Oliveira; Denck Colman, Tiago Andre [UNESP]; Schnitzler, Egon; Demiate, Ivo Mottin (Springer, 2015)
Carioca bean is an important product of Brazil and its major components are protein and starch. In its native form, starch has some technological constraints and modifications can improve its properties. Acetylation facilitates water percolation in amorphous regions, and hydroxypropylation improves water penetration. The aim of this study was to evaluate the effects of acetylation and dual-modification on the properties of starch from Carioca beans (Phaseolus vulgaris L.). The native starch was modified by acetylation and dual-modification (acetylation and hydroxypropylation) and then analyzed by SEM, X-ray diffractometry, FT-IR spectroscopy, DSC, TG, pasting properties, and syneresis. The modifications did not change the shape, size, and surface of the starch granules, although they affected their amorphous regions. FT-IR bands presented a peak at 1,732 cm(-1), which was assigned to acetylation, and another at 2,974 cm(-1), which was due to hydroxypropylation. TG-DTA curves showed typical behavior of starches with three mass losses. DSC curves showed an increase in the enthalpy to gelatinisation for sample (b) and a reduction for sample (c). RVA curves showed a reduction in the initial temperature, an increase in peak viscosity, and breakdown and setback after modifications. The acetylated starch showed higher freeze-thaw stability; however, syneresis was higher for the dual-modified starch.
Keywords: Bean starch; Thermal analysis; Dual modified; Acetylated starch, hydroxypropylated starch